Desenvolvimento de um sistema de controle ativo de ruído de baixo custo - Zuffi, Geisa Arruda (2017)
The search for alternatives that compatibilize acoustic, thermal and luminous performance made the use of ventilated acoustic frames gain prominence. However, those available on the market have limited performance at low frequencies, since they are only equipped with passive noise control techniques, making it necessary to research new technologies that are capable of eliminating this deficiency. In this context, the present work evaluated the implementation of active techniques of noise control in acoustic shutters, through the use of piezoelectric materials. For this, a numerical analysis of the noise attenuation promoted by different venetian configurations and by different locations for the performance of the control was made, aiming to choose the combination between them capable of offering the best increment in noise attenuation. Then, an experimental evaluation was carried out to prove the applicability of the proposed system. The experimental results indicate the ability to attenuate 18 dB at the exit of the shutter on the range of frequency analyzed.